IDENTIFIKASI FAKTOR GLASS CEILING PADA PEREMPUAN PENDETA - Purba, Elva Rini; Andriyanto, Andriyanto (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2023)
The Reformed Church reconstructed a new identity for women as equal to men. The church reforms provided a bridge to the acceptance of women as pastors. If pastoral status is no longer a major issue in most denominations, the structural strategic status of the church is not. The number of women pastors who have succeeded in occupying structural strategic positions is still low. This condition indicates the occurrence of a glass ceiling. Glass ceiling is a metaphor that describes the existence of an invisible barrier in the form of a glass ceiling that prevents minorities such as women from occupying strategic positions.This paper is intended to identify the factors that contribute to the glass ceiling in women pastors. Identification was conducted using the qualitative method of a literature review of several journals and books. The results revealed that there are four glass ceiling factors. The first is the internal factor, self-efficacy (self-confidence, intention to persevere and self-development, ambition, education and experience, adaptability, and cognitive ability). Second is institutional/organizational factors (work environment), such as masculine work environment and culture,